Pengaruh E-Trust Dan E-Satisfaction Terhadap Minat Pembelian Ulang Konsumen Shopee - Dianti, Muthia Rahma; Rahim, Hamidah; Zulstra, Jum’adil Dwi; Rizalina, Rizalina (LPPM Universitas Dharma Andalas, 2024)
Industrial revolution 4.0, the introduction of the internet, and smartphones have proven to be stimulants in changing online consumer behavior in the digital era. Demand for products through buying and selling online is increasing. This study aims to see (1) the effect of e-trust on the repurchase intention of Shopee consumers. (2) the effect of e-satisfaction on the repurchase intention of Shopee consumers. The questionnaire was developed for 123 Shopee consumers who had shopped at least once and registered on Shopee user accounts. Quantitative research methods used survey methods and analyzed using multiple regression analysis. The results of this study indicate that (1) E-trust had a significant effect on the repurchase intention of Shopee consumers. (2) e-satisfaction had a significant effect on the repurchase intention of Shopee consumers. Consumer e-trust and e-satisfaction are very important factors as determinants in retaining customers.